Virulence of Phytophthora isolates from Piper nigrum L. and their sensitivity to metalaxyl-mancozeb - R. Suseela Bhai, K.B. Vinitha, M. Anandaraj and (Journal of Plantation Crops, 2016)
Foot rot disease caused by Phytophthora capsici in black pepper is the most destructive disease. A total of 82 isolates from the National Repository of Phytophthora at ICAR-Indian Institute of Spices Research were evaluated for their sensitivity to metalaxylmancozeb and also tested for their virulence. Of the 82 isolates studied, 19 (23.2%) were highly sensitive to metalaxyl-mancozeb and six (7.3%) were comparatively insensitive (EC90 value >40 ppm; range 41.3 to 68.5 ppm). The isolates also varied in the degree of virulence, viz., 34 (41.5%) were highly virulent, 39 (47.6%) moderately virulent, 4 (3.7%) mildly virulent, and 5 (6.1%) non-virulent. There was neither any significant correlation between sensitivity to metalaxyl-mancozeb and virulence nor with the geographical location.Â